2021
DOI: 10.3390/ijerph18136921
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Total Number of Residential Fire-Related Incidents and Underreported Residential Fire Incidents in New South Wales, Australia by Using Linked Administrative Data

Abstract: The rate of fires, and particularly residential fires, is a serious concern in industrialized countries. However, there is considerable uncertainty regarding the reported numbers of residential fire incidents as official figures are based on fires reported to fire response agencies only. This population-based study aims to quantify the total number of residential fire incidents regardless of reporting status. The cohort comprised linked person-level data from Fire and Rescue New South Wales (FRNSW) and health … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…They found that there were 6.56 fires per hundred households per year of which 96.7 % are not attended by the fire department. Similar results have been found for the United Kingdom [7] and Australia [8][9][10] [11]. The results from [7]- [10] were that 75 % of fires are unattended by the fire service, while [11] found that 85 % of injury-inducing fires were unattended by the fire service.…”
Section: Firesupporting
confidence: 77%
See 1 more Smart Citation
“…They found that there were 6.56 fires per hundred households per year of which 96.7 % are not attended by the fire department. Similar results have been found for the United Kingdom [7] and Australia [8][9][10] [11]. The results from [7]- [10] were that 75 % of fires are unattended by the fire service, while [11] found that 85 % of injury-inducing fires were unattended by the fire service.…”
Section: Firesupporting
confidence: 77%
“…The association is likely the person being intimate with the fire in many cases. In general, though, the deadliness of a fire is correlated with its size [12], while recent research [11] suggests that most injury-inducing fires are not reported to the fire department, which in turn suggests that most injuries occur in relatively small fires.…”
Section: Peoplementioning
confidence: 99%
“…Fire incidents that were not reported to or attended by FRNSW were not included in this study. This suggests that the burden of deaths and injuries associated with residential fire incidents are an underestimated of the true number as demonstrated by the authors elsewhere ( Ghassempour et al, 2021 ).…”
Section: Limitationsmentioning
confidence: 79%
“…The datasets and linkage have been detailed elsewhere ( Harvey et al, 2020 , Ghassempour et al, 2021 ).Ethical approval for this study was obtained from the NSW Population and Health Services Research Ethics Committee (HREC/16/CIPHS/36) and Western Sydney University Human Research Ethics Committee (RH12399).…”
Section: Methodsmentioning
confidence: 99%
“…The calculated temperature and smoke field distribution at the fire site were consistent with the reports of the fire department 10 . Ghassempour et al found that fires in socio-economically disadvantaged areas among males and adults were often overlooked and not reported 11 . Jonsson et al found that fatal residential fires more often originated in the bedroom, were more likely to occur at night, and were more often caused by smoking in Sweden 12 .…”
Section: Research Motivationmentioning
confidence: 99%